ENGLISH STUDENTS’ DIFFICULTIES ON TOEFL TEST; A CASE STUDY - Risa Anggraini; Juliana Juliana; Cindy Dwi Syafitri; Fiore Arayu Hutagalung (Sean Institute, 2023)
The ability of students to master English is often determined by the results of an English proficiency test, namely the Test of English as a Foreign Language (TOEFL). TOEFL is an English language test that measures a person's level of English proficiency through listening tests, writing and structured expressions, and reading tests. However, when taking the TOEFL test, students frequently encounter numerous obstacles in attaining high marks, which can be attributed to a lack of preparation. The goal of this study was to explore the difficulties that students encountered when taking the TOEFL test. Three students were involved in this study, they were the eighth semester students majoring in English education study program at one private university in Medan. A qualitative case study was used in the formulation of this research approach. In depth-interview was used to obtain data in this study. Based on the data collected, there were several major themes such as 1) Students’ difficulties on TOEFL Test, 2) Students’ strategies utilized to overcome problems on TOEFL test, and 3) Students’ motivation to minimize mistakes on TOEFL test. Keywords; English Education Students, Students’ Difficulties, TOEFL Test.